Analyzing Role of Emotional Intelligence Learning in Ball Games for Promoting Students’ Quality Education - Liu Hongyu (Revista de Psicología del Deporte (Journal of Sport Psychology), 2021)
Emotional intelligence education has become a critical element in China's education reform and for the implementation of quality education. This paper attempted to examine how Emotional intelligence learning in ball games can make a strong positive impact on ball games and play a vital role in students' future life. The paper also highlights that a higher emotional intelligence can help students deal with destructive emotions. There are competition and cooperation in ball games, which are full of psychological and physical challenges. The school advocates a collective activity that requires the unity and harmony of all members through active collaboration. The collective spirit also requires teachers to cultivate the spirit of cooperation and competition among students, who can correctly handle collaboration in the game and form an improvement of emotional intelligence learning. In the process of teaching ball games, middle school teachers always infiltrate dynamic intelligence education and guide students to recover their emotional intelligence in competition. This paper has profoundly examined the leading role of psychological intelligence training in ball games in promoting quality education for students, thus better helping students play their due competitive role and cultivate higher overall quality.